Mindfulness Supports Maternal Mental Health - Ellyzabeth Sukmawati; Titi Alfiani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the role of mindfulness in supporting maternal well-being. It adopts a qualitative research approach through a systematic literature review. The data used are secondary sources obtained from a variety of scientific materials, including indexed national and international journal articles, academic books, research reports, dissertations, theses, and official publications from related institutions. Scientific journal articles published between 2020 and 2025 are collected from leading databases such as PubMed, Scopus, ScienceDirect, PsycINFO, and Google Scholar. Recent literature highlights mindfulness as a promising intervention to improve maternal well-being during pregnancy. It offers psychological benefits, supports physiological regulation, and strengthens the bond between mother and baby. mindfulness as a promising intervention to improve maternal well-being during pregnancy. It offers psychological relief, physiological regulation, and a stronger mother-baby connection. However, more rigorous, inclusive, and long-term research is needed to fully understand this potential and optimize its application in prenatal care. Although the benefits of mindfulness during pregnancy are promising, there are limitations in the amount of research currently available. Many studies rely on self-reported measures, which may be susceptible to bias. Sample sizes are often small and may lack diversity in terms of race, socioeconomic status, or previous mental health conditions. In addition, not all mindfulness interventions are standardized, which makes it difficult to compare results across different studies.